Postnatal Ontogeny of the Cranial Base and Craniofacial Skeleton in Male C57BL/6J Mice: A Reference Standard for Quantitative Analysis - Vora, Siddharth R.; Camci, Esra D.; Cox, Timothy C. (Frontiers in Physiology, 2016)
Growth of the craniofacial skeleton is a complex process controlled by both genetic and epigenetic factors, perturbations of which can lead to varying degrees of dysmorphology. Mouse models that recapitulate clinical craniofacial phenotypes are instrumental in studying the morphogenetic progression of diseases as well as uncovering their genetic and molecular bases. Commonly encountered phenotypes in these models include defects in the cranial base synchondroses, calvarial sutures, mandible or the midface, or any combination thereof, with the concurrent presence of altered overall craniofacial growth. However, the literature lacks an adequate normative timeline of developmental events and growth trends that shape the mouse craniofacial skeleton. In this report, we analyzed the postnatal craniofacial ontogeny (from postnatal day 7 [P7] through to P112) of male mice from the most widely used inbred mouse strain, C57BL/6J, using high-resolution microcomputed tomography (μCT) in combination with classic morphometric approaches. We also evaluated cranial base synchondroses at the histological level, and compared it to μCT-generated data to assess the timing and pattern of closure of these structures. Our data underscore the complex and unique growth patterns of individual bones and cranial regions and highlight the need to include younger animals in studies aimed at analyzing craniofacial growth processes. Furthermore, these data serve as a reference standard for future quantitative work.